Cutaneous MMPs are differently modulated by environmental stressors in old and young mice - Fortino, Vittoria; Maioli, Emanuela; Torricelli, Claudia; Davis, Paul; Valacchi, Giuseppe (Toxicology letters, 2007)
Skin is frequently exposed to pro-oxidative insults such as UV light, ozone (O 3) and cigarette smoke (CS), which are able to deplete antioxidants and induce oxidation products affecting skin pathophysiology. Skin turnover and regeneration are largely dependent on extracellular matrix metabolism, which is under the control of matrix metalloproteinases, MMPs. The present study evaluated cutaneous MMPs activity upon environmental pollutants exposure and analyzed the response of old and young animals. For this purpose, SKH-1 hairless mice (8 weeks and 18 months old) were exposed for 6 h/day to 0.25 ppm of O 3 or to UV radiation (0.3 MED) or to CS for 4 days. Gelatin zymography revealed an increase of MMP-2 in both young and old animals, after exposure to pollutants, while MMP-9, undetectable in unexposed subjects, was strongly induced only in old mice. Casein zymography and Western blot analysis showed an increase of MMP-12 in the aged group after environmental stressors exposure. TIMP-1 and -2 expression levels did not change. The current study demonstrates the ability of certain environmental pollutants to affect the ECM turnover through modulation of specific MMPs, and confirms the higher susceptibility of old subjects to exogenous pro-oxidant insults.